Preliminary evaluation of an e-module with problem-based learning for improving junior high school students’ understanding of the digestive system - Putri, Nur Diana; Mellisa, Mellisa; Hidayati, Nurkhairo (Jurnal Edukasi Biologi, 2026)
This study aims to conduct a preliminary analysis of the need for developing Problem-Based Learning (PBL)-based e-modules on the digestive system for grade VIII junior high school students. The lack of interactive learning media and the dominance of conventional methods lead to a low understanding of students’ concepts in abstract materials. This type of research is descriptive, using both quantitative and qualitative approaches. The data collection instruments included a needs questionnaire distributed to 12 students of grade VIII.7 at SMPN 25 Pekanbaru and structured interviews with two science teachers. The results of the questionnaire analysis showed that the need for digital teaching materials was in the category of quite good (56.25%), but the indicators of the use of the PBL model (15.90%), the attractiveness of the display (13%), and the interactive features (10.10%) were in the very poor category. The results of the interviews revealed that students had difficulty visualizing the mechanisms of digestive organs and enzymes through printed books. The teacher emphasized the need for digital media that integrates contextual issues to stimulate critical thinking. The results of this study suggest that developing Problem-Based Learning (PBL)-based e-modules on materials related to the digestive system should be considered an alternative learning medium to improve learning quality and students’ understanding of concepts.